Data Mining Pada Faktor-Faktor Potensi Daerah di Kabupaten Sidoarjo Provinsi Jawa Timur - Lestari, Trianingsih Eni; Permadi, Hendro; Susilowati, Sri (Jurnal Matematika; Vol 10 No 2 (2020), 2020)
Abstract : Sidoarjo is one of the districts located in East Java that has developed rapidly. The remarkable progress can be achieved due to several potentials had by its people, for instance, industries, trades, small and medium businesses. Therefore, this research aims to find out the information regarding dominating factors had by the Sidoarjo using data mining. The result shows that Keboansikep, Sawotratap, Tebel, Keboananom, Gedangan, Keboguyang, Ketajen, Sidomulyo, Terik, Ponokawan, Sedengan Mijen, and Barengkrajan villages are the most potential villages in Sidoarjo. Based on the classification method, it is found that the villages of Keboansikep, Sawotratap, Tebel, Keboananom, Gedangan, and Ketajen (Gedangan District) have local potential in the form of agricultural factors such as rice and secondary crops. All residences in Keboguyang Village (Jabon District) already have an IMB. Meanwhile, the villages of Sidomulyo, Terik, Ponokawan, Sedengan Mijen, and Barengkrajan (Krian District) have high early childhood education factors such as kindergarten students, kindergarten teachers, and kindergarten schools Keywords : Data Mining, Local Potential, Biplot analysis